Economic impact of climate change: simulations with a regionalized climate-economy model - Oliver Deke; Kurt Georg Hooss; Christiane Kasten; Gernot Klepper; Katrin Springer (Kiel Institute of World Economics (IfW), 2001)
Climate change affects the physical and biological system in many regions of the world. The extent to which human systems will suffer economically from climate change depends on the adaptive capabilities within a region as well as across regions. We use an economic General-Equilibrium model and an Ocean-Atmosphere model in a regionally and sectorally disaggregated framework to analyze adaptation to climate change in different regions of the world. It turns out that vulnerability to climate impacts differs significantly across regions and that the overall adjustment of the economic system quite reduces the direct climate impacts.
Keywords: O41; Q17; Q24; R53; D58; O13; 330; computable general equilibrium model; integrated assessment framework; impact modelling; ocean-atmosphere model; climate change; Klimaveränderung; Wirtschaftliche Anpassung; Weltwirtschaft; Internationale Wirtschaftsbeziehungen; Allgemeines Gleichgewicht; Ökonometrisches Makromodell; Mehr-Sektoren-Modell; Dynamisches Modell; Theorie; Welt